Content Analysis of English Classroom Interactions to Identify Patterns of Instructional Language Use and Student Engagement - Mohd. Rafi Riyawi; Nur Aisyah Zulkifli (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates patterns of instructional language use and student engagement in English classroom interactions during the 2022–2024 academic period, a time marked by shifting educational priorities toward digital learning integration and increasing demands for student-centered pedagogy. The purpose of this research was to examine how features of teacher talk—such as questioning strategies, scaffolding, feedback types, and discourse management—shape learners’ behavioral and verbal engagement during classroom activities. The study draws upon interactional competence theory, sociocultural learning theory, and classroom discourse analysis to understand how instructional language mediates student participation. The study applies a qualitative content analysis approach supported by NVivo-assisted coding to identify recurring patterns within English classroom interactions. Rather than relying exclusively on quantitative language indicators, the analysis focuses on interpreting interactional meanings, discourse structures, and thematic patterns derived from transcribed classroom recordings. Teacher utterances and student responses were coded through iterative cycles—open, axial, and selective coding—to ensure systematic categorization and enhanced coding reliability. Indicators of student engagement (responsive, voluntary, and collaborative engagement) were treated as qualitative attributes that contextualized the relationship between instructional language features and participation dynamics. Instead of conducting statistical modeling, the study emphasizes narrative associations, interactional themes, and conceptual linkages to illuminate how instructional language facilitates or restricts engagement. The findings reveal that teacher talk dominates classroom discourse, with display questions, directives, and procedural instructions appearing most frequently. Classrooms with higher proportions of genuine questions, scaffolding strategies, and elaborative feedback exhibited noticeably greater voluntary and collaborative engagement. In contrast, directive-heavy interactional patterns produced shorter student responses and limited opportunities for dialogue. NVivo analysis identified three overarching themes—interactional dominance, limited dialogic space, and uneven engagement distribution—indicating persistent challenges in implementing student-centered learning. The study concludes that instructional language plays a significant role in shaping the depth and distribution of student engagement in English classrooms. Strategic use of questioning, scaffolding, and feedback enhances learner participation and creates a more interactive learning environment. These findings highlight the importance of discourse-focused pedagogical development to support student-centered learning and improve interactional quality in Indonesian EFL classrooms.